2016
DOI: 10.1155/2016/7214020
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Tenofovir-Based Combination Therapy versus Tenofovir Monotherapy in Chronic Hepatitis B Patients Presenting with Suboptimal Responses to Pretreatment: A Meta-Analysis

Abstract: Background/Aims. It remains unclear whether tenofovir disoproxil fumarate- (TDF-) based combination therapy produces better outcomes than TDF monotherapy in chronic hepatitis B (CHB) patients. The aim of this study was to compare the efficacy of the two regimens by performing a meta-analysis. Methods. A comprehensive literature search was performed on the comparison of TDF-based combination therapy and monotherapy for CHB patients in the PubMed, Embase, Web of Science, and the Cochrane Libraries. Both dichotom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…In a related analysis, we noted a signi cant improvement in biochemical parameters in both groups. In most studies, the biochemical response in patients treated with TDF and TDF+LAM is similar (53).…”
Section: Discussionmentioning
confidence: 96%
“…In a related analysis, we noted a signi cant improvement in biochemical parameters in both groups. In most studies, the biochemical response in patients treated with TDF and TDF+LAM is similar (53).…”
Section: Discussionmentioning
confidence: 96%
“…Longer treatment was associated with higher HBeAg and HBsAg loss or seroconversion [2]. Therefore, combination therapy with drugs from other classes is suggested although longer-duration studies conducted by Liang et al [13] and Chen et al [15] reported that both TDF monotherapy and TDF-based combination therapy possessed good efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Many literatures stated that TDF has good efficacy and safety. However, several adverse events have been reported such as renal toxicity and bone demineralization [6], [7], [15]. Other disadvantages of nucleotide analogs in treating CHB are indefinite duration of treatment, risk of developing resistance, and less HBeAg and HBsAg conversions [9], [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination therapy did not increase drug-related adverse events [31], but increased economic burden is another issue among treated patients. Although generic drugs have been released, combination therapy doubles the cost.…”
Section: Discussionmentioning
confidence: 99%